La terminología en la práctica profesional de la interpretación. implicaciones didácticas - Vanhecke, Katrin (Anales de Filología Francesa, 2010)
This article illustrates the use of terminology in the professional practice of interpreting and explains some pedagogical applications of terminological preparation within the framework of the European Space for Higher Education. To begin with, the paper describes the functions of terminology in the interpreting practice. It describes the difficulties of comprehension and translation of specialized vocabulary encountered by professional interpreters in their daily practice. It presents the result of a classroom practice preparing a multilingual glossary for the UN Summit on Climate Change in Copenhagen in December 2009.